Positioning control of liquid crystal elastomer actuator based on double closed-loop system structure. (June 2022) - Wu, Jundong; Wang, Yawu; Ye, Wenjun; Su, Chun-Yi
Abstract: This paper proposes a control strategy with a double closed-loop system structure to achieve the positioning control of the photo-responsive liquid crystal elastomer (LCE) actuator. This work helps developing photo-responsive soft robot applications that are totally different from conventional electro-driven ones. In the proposed strategy, the outer loop is a combination of a PID controller in parallel with a feed-forward controller, the PID controller ensures that the positioning control target can be reached, and the feed-forward controller is an inverse model of the temperature-deformation relationship of the LCE actuator developed recently, to calculate the target temperature of the LCE actuator. The inner loop is a PID controller, which ensures that the temperature of the LCE actuator converges to the target value calculated by the feed-forward controller. Parameters of the inner PID controller are tuned using a simulation-experiment combined method based on the Hammerstein–Wiener model, and parameters of the outer PID controller are tuned based on experiments. Experiments are performed to show the effectiveness of the proposed method, and comparisons are made with conventional single closed-loop control structure. Such a double closed-loop structure has faster response and higher accuracy, and it lays a basis for possible photo-responsive soft robot applications. Highlights: A double closed-loop structure is proposed to achieve the positioning control of LCE actuator. The outer loop is a combination of a PID controller in parallel with a feed-forward controller. The inner loop uses a PID controller to track the target temperature of LCE actuator. The outer loop is used to track the target displacement of LCE actuator. The double loop structure has better control performance than conventional single loop structure.